Increasing the productivity and profitability of pearlmillet through frontline demonstration in dryland areas of Rajasthan - Bamboriya, Mrs. Sumitra Devi Bamboriya; Jat, Dr. A.S. Jat; Choudhary, Dr. Mamta Devi Choudhary; Dr. L.R. Choudhary (Annals of Arid Zone, 2023)
The present study was carried out to evaluate the performance of improved variety with scientific package of practices on productivity and profitability of pearlmillet under moisture stress conditions. Frontline demonstrations (FLDs) were conducted during Kharif, 2018 to 2022 in total of 50 ha area with 125 demonstrations by evaluating the performance of MPMH-17/HHB-299 variety with improved package and practices. Under demonstration the grain yield of pearlmillet was increased by 16.42-23.40 per cent over farmer’s practice. The extension gap, technology gap and technology index were calculated as2.00-5.03q ha-1, 1.47-16.20 q ha-1 and 5.25-57.86per cent, respectively. For obtaining profitable yield of pearl millet farmers should apply recommended dose of fertilizers, used improved hybrid seed, integrated weed management, water management and insect-pest management. Conducting of frontline demonstrations on farmers field also help to identify the constraints and potential of the pearl millet in that specific area in realizing the food security as well as it helps in improving the economic and social status.